The influence of demographic and lifestyle factors on blood donation delay among student population: a retrospective study - Feng, Wang; Yun, Wang; Le, Wang; Zhi-guo, Xu; Hai-ying, Yang; Shu-fang, Wu; Zhen-yan, Wei; Yi-zhu, Chen; Quan, Sun; Jing-xian, Fei (Frontiers in Public Health, 2023)
Objective This study analysed blood donation deferral trends, reasons and demographic/lifestyle characteristics among students in Huzhou City. The aim was to understand the health status of students and reduce the deferral rate. Methods Data on blood donation deferral among students in Huzhou City from 2018 to 2022 were collected and analysed. Deferral trends and main reasons were investigated. Using demographic and lifestyle data from 2,619 cases in 2022, a risk prediction model for deferral was constructed. Results The deferral rate among students in Huzhou City from 2018 to 2022 was 12.60% (p = 0.000, 95%CI: 12.14–13.06%), showing a significant increasing trend. Temporary deferral was the main reason, with alanine aminotransferase (ALT), blood pressure (BP) and haemoglobin (Hb) as the main deferral factors. ALT had a deferral rate of 5.23% (4.92–5.53%), BP 3.30% (3.06–3.55%), and Hb 2.92% (2.68–3.15%). Demographic and lifestyle characteristics in 2022 showed no significant differences between education level, household registration and deferral rate (p > 0.05). However, age, sex, blood donation history, sleep quality, diet and mental state had variable effects on ALT, BP, and Hb deferrals (p < 0.05). Logistic regression showed that sex, blood donation history, sleep quality, diet and mental status were independent risk factors for ALT deferral (p < 0.05), with odds ratios (ORs) of 5.057, 2.735, 1.594, 3.679, and 1.957, respectively. Age, blood donation history, sleep quality and mental state were independent risk factors for BP deferral (p < 0.05), with ORs of 0.256, 3.658, 6.042, and 1.812, respectively. Gender, blood donation history and diet were independent risk factors for Hb deferral (p < 0.05), with ORs of 0.244, 0.542, and 3.103, respectively. Conclusion Students’ health problems require attention. Effective health education should improve self-health management and pre-donation health behaviour to encourage regular blood donation.